Drug Utilization Pattern among Stroke Patients – A Cross-sectional Insight (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: This study aimed to evaluate drug utilization pattern among stroke patients. Materials and Methods: Across-sectional study was conducted among 96 stroke patients aged from 30 to 92 years in a hospital in Malaysia.A total of 88 patients were available for descriptive analysis and logistic regression analysis. Descriptive andlogistic regression analyses were performed. Results: On average, patients were aged 67.62 years (standarddeviation of 13.14) and had a higher incidence in Malay ethnicity (42.7%). Ischemic stroke accounts for 91.67%of the study, with a slightly higher proportion of female patients (51.04%). Majority of stroke patient complaintgeneralized body weakness as their major symptom (19.81%). Calcium channel blocker was found to be the mostused antihypertensive agent among stroke patients (40.9%) followed by angiotensin-converting enzyme inhibitors(ACEIs) (31.8%). Conclusion: Using logistic regression modeling, it was determined that the factors of a subjectwould affect the choice of prescribing of ACEIs and anticoagulant drugs.